The Effectiveness of Virtual Reality on Anxiety and Performance in Female Soccer Players - Kaitlyn Harrison; Emily Potts; Adam C. King; Robyn Braun-Trocchio (MDPI AG, 2021)
With the increased use of technology, relaxation interventions are finding their way into technology devices like virtual reality head-mounted displays (VR HMDs). However, there is a lack of evidence on the efficacy of VR relaxation interventions to reduce anxiety in athletes and how that is portrayed in their movement patterns. The purpose of the current study was to examine how a VR relaxation intervention affected perceived anxiety levels and penalty kick performance of female soccer players. Thirteen female soccer players took five penalty kicks in baseline, stress-induced, and VR relaxation conditions. Perceived levels of anxiety, self-confidence, mental effort, heart rate (HR), accelerometry of the lumbar spine and thigh, and performance in each condition was obtained. Results indicated that the VR intervention significantly reduced cognitive anxiety and somatic anxiety from baseline (p = 0.002; p = 0.001) and stress (p < 0.001; p < 0.001) with large effect sizes (Kendall's W = 0.72; 0.83). VR significantly increased self-confidence from baseline (p = 0.002) and stress (p = 0.001) with a large effect size (Kendall's W = 0.71). Additionally, all participants felt that VR helped them relax. Mental effort was significantly higher in the stress condition compared to that in baseline (p = 0.007) with moderate effect size (Kendall's W = 0.39). Peak acceleration and performance were not significantly influenced by stress or VR. This study serves as an initial step to evaluate VR relaxation interventions on performance in female soccer players.